Визначення структури та оцінка обсягів тіньової економіки в Україні - Линник, Олена Іванівна; Штучка, М. А. (НТУ "ХПІ", 2010)
The article is devoted to determination of the main theoretical issues of the shadow economy. Of considerable importance is the volume of assessment and examination of structural features of the shadow economy in Ukraine. Also considered dynamics of the shadow economy in percent of official GDP in the period from 2003 to 2009.
Keywords: ВВП; економіка прихована; економіка кримінальна; детінізація економіки